2008
DOI: 10.4161/org.6123
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro differentiation of uniparental embryonic stem cells into hematopoietic and neural cell types

Abstract: The biological role of genomic imprinting in adult tissue is central to the consideration of transplanting uniparental embryonic stem (ES) cell-derived tissues. We have recently shown that both maternal (parthenogenetic/gynogenetic) and paternal (androgenetic) uniparental ES cells can differentiate, both in vivo in chimeras and in vitro, into adult-repopulating hematopoietic stem and progenitor cells. This suggests that, at least in some tissues, the presence of two maternal or two paternal genomes does not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
(118 reference statements)
1
5
0
Order By: Relevance
“…While PG ES cell chimeras can survive postnatally with substantial contribution of ES cells (Sturm et al, 1994), AG ES cell chimeras typically exhibit severe defects and high lethality during fetal and postnatal stages (Mann et al, 1990;Narasimha et al, 1997). However, similar to ES cells derived from biparental (N) embryos, uniparental ES cells generate ecto-, meso-, and endodermal cell lineages in cell cultures including neural progenitor/stem cells and engrafting hematopoietic stem cells Eckardt et al, 2008;Eckardt et al, 2007;Lengerke et al, 2007;Teramura et al, 2009). We consider the analysis of AG ES cells relevant for two reasons: 1.)…”
Section: B C Dmentioning
confidence: 99%
“…While PG ES cell chimeras can survive postnatally with substantial contribution of ES cells (Sturm et al, 1994), AG ES cell chimeras typically exhibit severe defects and high lethality during fetal and postnatal stages (Mann et al, 1990;Narasimha et al, 1997). However, similar to ES cells derived from biparental (N) embryos, uniparental ES cells generate ecto-, meso-, and endodermal cell lineages in cell cultures including neural progenitor/stem cells and engrafting hematopoietic stem cells Eckardt et al, 2008;Eckardt et al, 2007;Lengerke et al, 2007;Teramura et al, 2009). We consider the analysis of AG ES cells relevant for two reasons: 1.)…”
Section: B C Dmentioning
confidence: 99%
“…GFP is one of several proteins that can be fused to a native protein and inserted into the genome to trace and detect donor cells in the host tissue with high sensitivity and stability (Eckardt et al, 2008;KanatsuShinohara et al, 2008;Oda et al, 2009). However, several studies have demonstrated the limitations of this method (Liu et al, 1999), as GFP can alter development and mature function, especially when expressed at high levels (Ho et al, 2007;Mawhinney et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent fusion proteins are a powerful method to detect donor cells and proteins in the tissues and organs of the host (Lippincott-Schwartz et al, 2001;Yang et al, 2005;Giepmans et al, 2006;Shaner et al, 2007;Shcherbo et al, 2007). GFP is one of several proteins that can be fused to a native protein and inserted into the genome to trace and detect donor cells in the host tissue with high sensitivity and stability (Eckardt et al, 2008;Kanatsu-Shinohara et al, 2008;Oda et al, 2009). However, several studies have demonstrated the limitations of this method (Liu et al, 1999), as GFP can alter development and mature function, especially when expressed at high levels (Ho et al, 2007;Mawhinney et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, they can be used to match a substantial bigger number of patients needing cell-based transplant and has a higher successful rate than with hESC when only partial matches were possible. On the other hand, the uniparental tissues were suggested to result in unbalanced expression of the imprinting genes [20] and the loss of imprinting genes or false expression profile may eventually lead to some diseases [21] or increased tumor risk by expanding the target cell population and/or modulating the effect of the subsequent genetic alterations on these cells. Some of the hPG ESC gene expression profile data revealed that the maternal and/or paternal imprinting genes expression were absent, but others such as the International Stem Cell Corporation (ISCO) stated that they had not found evidence of imprinting issues, at least in vitro.…”
Section: Imprinted Genementioning
confidence: 98%